Sectarian Competition and the Market Provision of Human Capital. (9th March 2023) - Xiong, Heyu; Zhao, Yiling
Abstract : We study the role of denominational competition in the expansion of higher education in the nineteenth-century United States. We document that nearly all colleges established in this period were affiliated with a Christian denomination. Empirical analysis reveals a robust positive relationship between the denominational fragmentation of the county and the number of colleges established. We take several steps to rule out competing explanations and also highlight the causal channel by utilizing two historical case studies. We conclude by estimating a model of school choice and showing that students exhibited strong preferences to attend same-denominational colleges in terms of willingness-to-pay and willingness-to-travel. Therefore, we argue that religious diversity softened the extent of tuition competition between institutions and precipitated an "excess" entry of schools.